Terrorism Law Enforcement In Indonesia: Integrating Pancasila In The Fight Against Modern Threats - Muhamad Zarkasih; G M Hatta; Timbo Mangaranap Sirait (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2025)
The evolving threat of terrorism in Indonesia has driven the development of counterterrorism laws to address both domestic and international activities. Since the 2002 Bali bombings, Indonesia has enacted legal frameworks, including Law No. 15 of 2003 and its amendment, Law No. 5 of 2018. However, concerns have arisen regarding human rights violations, particularly in detainee treatment, preventive detention, and arbitrary arrests. This study employs a qualitative approach, utilizing doctrinal legal analysis and empirical data from interviews with legal experts, policymakers, and practitioners. It assesses the compatibility of Indonesia’s counterterrorism laws with international human rights standards, emphasizing Pancasila’s core values—social justice, unity, and human dignity. Key challenges include inadequate oversight mechanisms, insufficient deradicalization programs, and the rise of online radicalization. The study recommends integrating Pancasila principles into counterterrorism strategies, enhancing international cooperation, and ensuring that security measures respect individual rights. By addressing these issues, Indonesia can improve its counterterrorism effectiveness while maintaining its human rights commitment and fostering social justice.